Role of Active Versus Passive Complementary and Integrative Health Approaches in Pain Management - David Cosio PhD, ABPP; Erica Lin PharmD, BCACP (SAGE Publishing, 2018)
Background A general conclusion about the treatment of chronic, noncancer pain is that the results from traditional, passive modalities are disheartening. Perhaps this may be due to the propensity of patients to seek out passive versus active treatments. In pain management, active treatments should be the primary focus, with passive interventions as an adjunct. Objective The current study tested the hypotheses that Veterans would report a greater significant increase in active versus transitional and active versus passive complementary and integrative health (CIH) utilization after completing a formal pain education program. Methods The current study is a secondary analysis of existing data from an original study. The current study used a quasi-experimental, 1-group, pre-/posttest design. One hundred three Veterans completed a 12-week, "Pain Education School" program at a Midwestern VA Medical Center between November 4, 2011, and October 26, 2012. As part of the introduction and conclusion of the program, all Veterans completed a pre- and posteducation assessment which included an adaptation of the Complementary and Alternative Medicine Questionnaire©, SECTION A: Use of Alternative Health Care Providers measure. Results Significant differences were found between the pre- and posttest measures of use of active ( P  = .000) ( p <.001), transitional ( P  = .011), and passive ( P  = .007) CIH modalities. Conclusion The current findings suggest that an educational intervention in conjunction with the availability of treatment options has the potential to increase the use of those treatments. The current pain education program also seems to be aligned with the goal of pain self-management, which is to utilize more active interventions as a primary therapy.